Pengaruh Kualitas Pelayanan Dan Citra Produk Terhadap Loyalitas Pelanggan Pengguna Kartu Telkomsel Di Wilayah Surabaya - Nadya Vicky; Bambang Karnain; Achmad Daengs GS; Sugiharto Sugiharto; Rina Dewi (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study aims to determine the effect of service quality and product image on Telkomsel customer loyalty in Surabaya. The research method used is a quantitative method. Collecting data using a questionnaire distributed to the population of all Telkomsel card users in the Surabaya area, because this population is unlimited or the population cannot be determined with certainty. So this study uses a sample with the Lemeshow formula, namely 100 respondents. The data analysis technique used is the classical assumption test which consists of a normality test, heteroscedasticity test, multicollinearity test and multiple linear regression analysis, as well as hypothesis testing, namely the coefficient of determination test, f test, t test.The results of the research based on the resulting tests show that service quality and product image have a significant influence on Telkomsel customer loyalty in Surabaya, one of which is evidenced by the results of the coefficient of determination that the correlation between customer loyalty and all independent variables (service quality and product image) R -Square of 0.653 means that 65.3% variation or change in customer loyalty is jointly influenced by service quality and product image while the remaining 34.7% variation or change in customer loyalty is caused by other variables not included in this study.